Pendampingan Implementasi Sistem Informasi Akuntansi Berbasis Komputer Pada Toko Umat Koperasi Syari’ah Madani Banyumas Raya - Eko Suyono (Faculty of Economics and Business, University of Muhammadiyah Prof. DR. HAMKA, 2020)
This community service activity aims at providing assistance in the application of a computer-based accounting information system at “Toko Umat” the Banyumas Raya Syariah Madani Cooperative located at Jl. KS Tubun No. 14, Purwokerto Barat. This community service activity was carried out in the period May-October 2019 and was successfully carried out in accordance with the plan where the target of this activity has been achieved by implementing a computer-based information system designed by the PKM Team and partner organizations. It is expected that with computerized business management the partner will become more professional in managing it business. Keywords: Toko Umat, Computer-based Accounting Information System